Dominant versus non-dominant hand during simulated infant CPR using the two-finger technique: a randomised study - Debora Gugelmin-Almeida; Carol Clark; Ursula Rolfe; Michael Jones; Jonathan Williams (Resuscitation Plus, 2021)
Aims: The aim of this randomised study was to compare the two-finger technique (TFT) performance using dominant hand (DH) and non-dominant hand (NH) during simulated infant CPR (iCPR). Methods: 24 participants performed 3-min iCPR using TFT with DH or NH followed by 3-min iCPR with their other hand. Perceived fatigue was rated using visual analogue scale. Primary outcomes - (i) difference between DH and NH for compression depth (CCD), compression rate (CCR), residual leaning (RL) and duty cycle (DC); (ii) difference between first and last 30 s of iCPR performance with DH and NH. Secondary outcomes - (i) perception of fatigue between DH and NH; (ii) relationship between perception of fatigue and iCPR performance. Results: No significant difference between DH and NH for any iCPR metric. CCR (DH: P = 0.02; NH: P = 0.004) and DC (DH: P = 0.04; NH: P < 0.001) were significantly different for the last 30 s for DH and NH. Perception of fatigue for NH (76.8 ± 13.4 mm) was significantly higher (t = −3.7, P < 0.001) compared to DH (62.8 ± 12.5 mm). No significant correlation between iCPR metrics and perception of fatigue for DH. However, a significant correlation was found for CCR (r = 0.43; P = 0.04) and RL (r = −0.48; P = 0.02) for NH. Conclusion: No difference in performance of iCPR with DH versus NH was determined. However, perception of fatigue is higher in NH and was related to CCR and RL, with no effect on quality of performance. Based on our results, individuals performing iCPR can offer similar quality of infant chest compressions regardless of the hand used or the perception of fatigue, under the conditions explored in this study.